Two vegetation maps of the same island: floristic units versus structural units (Applied Vegetation Science, 1998)
Abstract. This paper presents a comparison of two alternative methods to describe and map vegetation: on the basis of plant species and growth forms, respectively. A stratified random sampling was taken from spontaneous vegetation in 1989 on the volcanic island of Pantelleria (near Sicily, Italy). Cartographic and other comparisons of the results from classification and ordination analysis suggest that the major differences were associated with differences in the time scale of the underlying processes. Species results (leading to floristic vegetation units) were representative of longer-term processes, growth-form results (leading to structural vegetation units) with shorter-term processes. Further implications of these results are discussed.